Juridical Analysis Of The Establishment Of Land Bank As An Agrarian Conflict Settlement - Kinanthi Sihutami, Veronica; Imanullah, Moch.Najib; Suraji, Suraji (Riviera Publishing, 2022)
Agrarian conflicts can occur between individuals and individuals or individuals with groups or business entities as well as with the government. Throughout 2020, there were 241 cases of agrarian conflict found. The existence of the Job Creation Law which also regulates land contains provisions for the existence of a Land Bank as an institution that can shelter abandoned lands of the state to be used for the prosperity of the people. In fact, a number of problems were found regarding the existence of this Land Bank which tends not to be able to bridge agrarian conflicts between parties. This study aims to describe how ineffective the Land Bank is in resolving agrarian conflicts. This research is a normative legal research with a qualitative approach. The results showed that the existence of a Land Bank with a non-profit principle actually benefited the private sector who wanted to use the land through the Land Bank. The absence of a Government Regulation concerning Land Bank also means that this institution does not yet have a legal umbrella to run. Utilization of abandoned land that can be taken by the state just like that is also considered to be impartial to the existence of farmers as small people, then it was found. in the control of a Land Bank, the benefits can be enforced and used in accordance with the actual procedure